Highly specific qPCR and amplicon sequencing method for detection of quarantine citrus pathogen Phyllosticta citricarpa applicable for air samples. (29th November 2022) - Zajc, Janja; Kogej Zwitter, Zala; Fišer, Sara; Gostinčar, Cene; Vicent, Antonio; Domenech, Anaïs Galvañ; Riccioni, Luca; Boonham, Neil; Ravnikar, Maja; Kogovšek, Polona
Abstract: The fungus Phyllosticta citricarpa is a quarantine pathogen in the EU and is of high economic importance in many parts of the world where favourable climate conditions drive the development of citrus black spot (CBS) disease. Disease symptoms include necrotic lesions on leaves and fruits. Low disease pressure can reduce crop marketability, while higher disease pressure can cause premature fruit drop, significantly increasing crop losses. The wind‐dispersed spores of P. citricarpa are especially problematic for rapid pathogen dispersal, but also provide an opportunity for early detection of the disease spreading into a new area. In this study we have developed and validated a quantitative PCR (qPCR) assay based on the TEF1‐α sequence. Specificity testing demonstrated that it is currently the only qPCR assay that does not cross‐react with closely related Phyllosticta species. The assay is sensitive and can detect a single copy of the TEF1 gene in a reaction, it is highly repeatable and reproducible and can be used for testing of the sticky tapes from spore traps as well as citrus fruit samples. High‐throughput sequencing (HTS) of the DNA barcodes ITS1 and TEF1 was also explored for the detection and discrimination of P. citricarpa . The limit of detection of the HTS was 1000 spores on a daily spore trap tape. This study makes an important improvement to the diagnostics of the CBS and the methods developed can also be applied to improve the surveillance and early detection of the pathogen when linked to spore samplers in the field. Abstract : Targeted and non‐targeted approach to detect causal agent of citrus black spot disease in air samples: specific qPCR assay and high‐throughput sequencing of two barcodes for detection and identification of Phyllosticta citricarpa .